Gnomic and paremiac fragments of the ''senno del ditto Dante'' in the Tuscan collections of short stories of the 14th-15th centuries (Carte Romanze, 2024)
The enduring influence of Dante and his literary oeuvre is palpable not only within the pinnacle of Italian literature’s most esteemed and refined genres but also within ostensibly lesser-regarded forms, such as short stories. This essay endeavors to explore the manifestation of Dante’s presence among Tuscan short story authors spanning the 14th to 15th centuries. Special emphasis will be placed on the gnomic and paremiac use of quotations derived from the Alighieri’s works.
Keywords: Dante, ser Giovanni, Sacchetti, Sercambi, Commedia, Pecorone, Trecentonovelle, Novelliere, short story, paroimia, sentence